THE ADAPTABILITY OF PESANTREN IN INDONESIA DURING THE NEW NORMAL ERA (JOURNAL OF INDONESIAN ISLAM, 2022)
This article discusses strategic issues of pesantren management during the Covid-19 pandemic-based “adaptation to new habit” era in Indonesia. The research is carried out to a total of fifteen pesantren in West Borneo, Yogyakarta, East Java, and West Java. Sociocultural perspectives of pesantren during this period also has influenced the emergence of adaptive protocols toward public interest (maṣlaḥah). Therefore, each pesantren has authentic regulations in dealing with the disasterous situation (sadd al-dharāi`). The results classify the adaptive responses of pesantren during the pandemic into three categories from the upper, middle, and lower tier management. Aside from misfortunes for humanity during the disaster, academics of pesantren suggest that they obtain several cocktails of wishful thinking from this phenomenon, i.e. inspiring ideas to maintain their faith and piety (hifẓ al-dīn) while developing enthusiasm for studying science and religion (hifẓ al-‘aql). To summarize, all observed pesantren have attempted to balance physical (żāhīrīyah) and emotional (baṭīnīyah) neccesities in overcoming the pandemic situation.